2015
DOI: 10.1016/j.jnucmat.2014.11.066
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effects of ion irradiation using nanoindentation techniques

Abstract: The effects of ion irradiation in materials for research are usually limited to a shallow surface layer of the order of one micrometre in depth. Determining the mechanical properties of such irradiated materials requires techniques with high spatial resolution. Nanoindentation is a relatively simple method for investigating these shallow layers with the advantage that statistically rich data sets for elastic and plastic property values can be generated. However, interpretation of the results requires and under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 31 publications
3
45
0
1
Order By: Relevance
“…(3) of the elastic modulus of the indenter E I and the actual elastic modulus of the material E S , using E I = 1141 GPa, υ I = 0.07 11) for a diamond tip and E S = 410 GPa 11) , υ S = 0.28 for W. Therefore it can be said that E S is associated with the true projected area of contact including pile-up A P EMC . Note that the symbols used in this study as shown in the List of Symbols are somewhat different from those in the original works by S. I. Bulychev [28][29][30][31][32] , or as in Heintze et al 21) , Beck et al 22) and Hardie et al 23) Heintze et al s 21) pileup corrected hardness method, which can be called as the elastic modulus correction (EMC) method, was assessed on unirradiated, neutron irradiated and self-ion-irradiated 9 mass% Cr f/m steel T91. An advantage of the EMC 21) method is that one actually does not have to measure the pileup height, but can use the latter expression of H EMC in eq.…”
Section: Pile-up Corrected Hardnessmentioning
confidence: 96%
See 4 more Smart Citations
“…(3) of the elastic modulus of the indenter E I and the actual elastic modulus of the material E S , using E I = 1141 GPa, υ I = 0.07 11) for a diamond tip and E S = 410 GPa 11) , υ S = 0.28 for W. Therefore it can be said that E S is associated with the true projected area of contact including pile-up A P EMC . Note that the symbols used in this study as shown in the List of Symbols are somewhat different from those in the original works by S. I. Bulychev [28][29][30][31][32] , or as in Heintze et al 21) , Beck et al 22) and Hardie et al 23) Heintze et al s 21) pileup corrected hardness method, which can be called as the elastic modulus correction (EMC) method, was assessed on unirradiated, neutron irradiated and self-ion-irradiated 9 mass% Cr f/m steel T91. An advantage of the EMC 21) method is that one actually does not have to measure the pileup height, but can use the latter expression of H EMC in eq.…”
Section: Pile-up Corrected Hardnessmentioning
confidence: 96%
“…Based on the ndings by Sneddon 27) as well as later on by other researchers, Bulychev, Alekhin, Shorokov and their co-workers [28][29][30][31][32] , Heintze et al 21) , Beck et al 22) and Hardie et al 23) recently proposed different methods for pile-up corrected hardness. In eq.…”
Section: Pile-up Corrected Hardnessmentioning
confidence: 99%
See 3 more Smart Citations